2013
DOI: 10.1080/03003930.2012.726198
|View full text |Cite
|
Sign up to set email alerts
|

Management Discretion and Political Interference in Municipal Enterprises. Evidence from Italian Utilities

Abstract: The attention of scholars and policy-makers is shifting from full privatisation to alternative measures as a means to improve the efficiency of public services. This article focuses on three restructuring measures adopted by local governments: partial privatisation (without transfer of control rights), inter-municipal joint ventures, and the presence of outside directors on the Board. Divergent hypotheses on these measures have emerged from two economic theories, namely public choice and the agency perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 52 publications
1
46
0
1
Order By: Relevance
“…BEL and FAGEDA (2010), when working on Spanish data, argued that inter-municipal agreements could be used as a way to reach scale economies for relatively small municipalities; while SORENSEN (2007), when working on Norwegian data, underlined the difficulties of managing the service when the ownership was very dispersed, as in the case of inter-municipal joint ventures. Consistently with Sorensen's analysis, GARRONE et al (2010) found for a sample of Italian utilities operating in gas, water, electricity and refuse collection in the years 1997-2006 a positive and significant impact of a proxy of Intermun on total costs. 31.…”
supporting
confidence: 80%
“…BEL and FAGEDA (2010), when working on Spanish data, argued that inter-municipal agreements could be used as a way to reach scale economies for relatively small municipalities; while SORENSEN (2007), when working on Norwegian data, underlined the difficulties of managing the service when the ownership was very dispersed, as in the case of inter-municipal joint ventures. Consistently with Sorensen's analysis, GARRONE et al (2010) found for a sample of Italian utilities operating in gas, water, electricity and refuse collection in the years 1997-2006 a positive and significant impact of a proxy of Intermun on total costs. 31.…”
supporting
confidence: 80%
“…In Europe these types of cooperation can take the form of joint corporations or administrative organizations where the different municipalities involved share ownership and production, as happens in Norway (Sørensen 2007), Finland (Haveri and Airaksinen 2007), Spain , the Netherlands (Bel et al 2010;Gradus et al 2014), and Italy (Garrone et al 2013). The collaborative may jointly produce a service or several services, contract it to one of the members, or contract to an outside party -for either profit or non-profit.…”
Section: What Is Cooperation?mentioning
confidence: 99%
“…Five studies, all large-N studies, find that mixed MOCs realise real efficiency gains (Bognetti and Robotti 2007;Filippini and Prioni 2003;Garrone, Grilli, and Rousseau 2013;Marra 2007;Pérez-López, Prior, and Zafra-Gómez 2015). Furthermore, three other studies, all small-N case studies, emphasise potential efficiency gains from mixed MOCs, but show that these could not come to long-term fruition due to goal conflict and negotiation problems (Da Cruz and Marques 2012;Marques and Berg 2011) or labour conflict (Swarts and Warner 2014).…”
Section: Mixed Mocsmentioning
confidence: 99%
“…Bel and Warner (2015) answer this in their review of studies on inter-municipal cooperation. First, Norwegian municipalities tend to be larger than those in Spain, leaving more economies of scale to be captured in Spain (while small localities were under-represented in the study of Garrone, Grilli, and Rousseau 2013). Second, joint MOCs in Spain are managed by a single authority to which municipalities delegate, while in Italy and Norway multiple municipalities are directly on the board of MOCs.…”
Section: Joint Mocsmentioning
confidence: 99%
See 1 more Smart Citation